Nilai-Nilai Pendidikan Seni Kuda Kepang Wahyu Krido Budoyo dalam Perspektif Pendidikan Buddhis - Istanto, Heni; Kustiani, Kustiani; Widiyono, Widiyono (Jurnal Pencerahan, 2018)
The purpose of the research is to describe the educational values of Wahyu Krido Budoyo kuda kepang folk art at village Lamuk in Buddhist educational perspective. The research was motivated by not know the value of the art of horses education braid as learning facilities for members. In addition, art benefits also work for the media learning informal education and supervision promiscuity in society. This research will answer the questions about model, implementation and impact of educacional values of Wahyu Krido Budoyo Kuda Kepang Folk Art in Buddhist educational perspective. Descriptive qualitative is the method used in this research. The research subjects included the manager and members of the art group while the object is the educational value. The technique of collecting data is by interview, observation, and documentation. The data authenticity was gained from the prolonged engagement, continuous observation, and triangulation. The data analysis was done through data collection, data reduction, data display, and conclusion. The results of the research are: (a) The education the art of covering the morality (sīlɑ) psychomotor aspect is manners, respect or appreciation, cooperation, discipline, orderliness, the motion and dance; concentration (samādhi) aspects affective the spirit, concern, responsibility, and tolerance; knowledge and wisdom (paññā) aspects cognitive the knowledge, creativity, and evaluation; (b) Application value education realized one of them through the exercise , staging , after staging , organization , and also social aspect; (c) The impact of the value of education namely members tended to build art become more responsible.